Analisis Pengaruh Store Atmosphere, Persepsi Harga, dan Kualitas Produk terhadap Kepuasan Pelanggan Pada Cafe Basabasi Yogyakarta - Fery Budi Setiawan; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of Store Atmosphere (X1), Price Perception (X2), and Product Quality (X3) on Customer Satisfaction (Y) Cafe Basabasi. This type of research is a quantitative research by taking samples from Cafe Basabasi customers as many as 100 people who have made purchases or visited Cafe Basabasi as research subjects. Sampling used purposive sampling technique, and data collection was carried out by survey method by distributing questionnaires. Data processing using SPSS version 25 application with data quality testing, classical assumption test, multiple regression test, t test and coefficient of determination test. Based on the test results in this study indicate that the variables Store Atmosphere, Price Perception, and Product Quality have a significant effect on customer satisfaction Basabasi cafe.